The 'perfect' gay man : an exploration of perfectionism with gay men in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Albany, New Zealand - Steadman, Jessica (Massey University, 2021)
This study explores the experiences of gay men in New Zealand who self-identify as perfectionists. The research had three aims: to explore how perfectionism is experienced throughout participants’ day-to-day lives, to understand how participants perceived their perfectionism to develop and change over time, and to investigate the self-perceived effects of perfectionism on participants’ relationships. Recruitment of participants was conducted with the support and assistance of Lesbian, Gay, Bisexual, Transgender, Queer plus (LGBTQ+) organisations using the snowballing method. Six individuals who identified as male, gay and perfectionistic participated in semi-structured interviews. The data was analysed using interpretative phenomenological analysis, with participants’ voices located centrally throughout the research. Participants’ accounts were integrated to form three overarching themes: Contributions to Perfectionism, Living with Perfectionism and Journey towards (Im)perfection. It was found that most participants viewed their sexual orientation as contributing to the development of perfectionism, as they sought to compensate for not fulfilling heteronormative standards. Further, participants reported that their perfectionism changed over their lifetime, shifting from being central to their identity to simply being a part of who they are. Participants also reiterated sub-themes related to both positive and negative effects of perfectionism, as well as increased acceptance of their perfectionism over time that mirrored their self-acceptance. These findings challenge current understandings of perfectionism through the inclusion of wider societal and cultural impositions in the development of perfectionism. Further, the way in which participants reported that perfectionism has shifted for them over their lifetimes provides a unique understanding of perfectionism as being potentially changeable in nature.
Keywords: Gay men; New Zealand; Psychology; Perfectionism (Personality trait); 440507 Studies of men and masculinities; 520599 Social and personality psychology not elsewhere classified